The Impact of COVID 19 In Digital Currencies Focused in Western Balkan Societies - Ermir Shahini; Eugen Skuraj; Fatbardh Sallaku; Shpend Shahini; Fabiola Bali; Ermira Kalaj; Elti Shahini (Indian Journal of Forensic Medicine & Toxicology, 2021)
Virtual communities’ emergence and innovative technologies bring up new types of accounting and transaction methods. These methods go beyond the existing economics knowledge and current legal solutions. Virtual societies develop and share their payment medium for goods and services exchange. The use of cryptocurrency has been enhanced during the COVID -19 era due to the health guidelines to minimize the virus’s spread. Cryptocurrencies bridge the loopholes left by the traditional currency in sorting crises like the Corona Virus pandemic. However, cryptocurrency brings up legal controversies that users are exposed to economic and legal risks.